Are we correctly measuring the rotational viscosity of heterogeneous bituminous binders?. (14th September 2020) - Giancontieri, Gaspare; Hargreaves, David; Lo Presti, Davide
Abstract : Modified bituminous binders allow asphalt technologists to design asphalt mixtures with superior performance. However, several recent studies highlighted that due to the complexity of these material, their characterisation can be challenging since common procedures used to characterise neat bitumen might not be adequate. For instance, during high temperature rotational viscosity testing of recycled tyre rubber modified binders (RTR-MB), a number of changes may occur to the sample leading to the here-defined sample stability which in turn provides misleading results. In this study the authors want to first provide a deeper understanding of this phenomenon by a numerical analysis using a bespoke Computational Fluid Dynamics (CFD) model to simulate the laboratory tests and use innovative visual aids to monitor the sample stability of heterogeneous bituminous binders during the rotational test. The numerical analysis was complemented by a laboratory campaign aiming at proving the occurring of sample stability during viscosity measurement of heterogeneous bituminous binders with a standard testing setup (SC-27). Furthermore, a dual helical ribbon (DHR) is here introduced as a solution to overcome the issue. Hence, laboratory tests were undertaken also with DHR and differences in viscosity measurements of neat bitumen, SBS-MB and RTR-MB were recorded. Results of this combined numerical and empirical approach proved that the standard setup for rotational viscosity measurements seems not be adequate for RTR-MB and depending on the level of modification and test temperatures, might not be best suited for SBS-MB either. The DHR seems to solve the issue and authors strongly recommend the adoption of this testing geometry to obtain more realistic high-temperature viscosity measurement of heterogeneous bituminous binders.